O estranho que habita em mim: impasses da adolescência na constituição da ideia de eu na contemporaniedade - Paula, Carolina Antonia Goulart de (2024)
This work has as a starting point a current social phenomenon that refers to a certain dissatisfaction shown by most adolescents with the image of their body. This perception was born from my clinical listening and found support in psychoanalytic theory to question some inherent impasses of adolescence and its relationship with body modifications through puberty, on the constitution of the idea of self. Thus, the impasses that will be portrayed in these works are: the mismatch between the image of the adolescent body and the social imperative of conforming the body to a certain aesthetic standard, which appears in contemporary times as a consistent and illusorily complete imaginary ideal; the arrival of puberty, given that the encounter with sexual non-knowledge permeates the adolescent body; the last deadlock, which appears as an outcome of the first and second deadlock discussed, refers to some teenagers who, despite seeking to meet a certain aesthetic ideal, are faced with the discomfort that permeates their body and causes a feeling of estrangement. The objective of this research is to interrogate adolescents’ deadlocks in constituting the idea of self in contemporary times, with a special focus on the estrangement of the body during puberty in this experience of subjectivation, through the perspective of Freudolacanian psychoanalysis. The research method is a qualitative theoretical study in psychoanalysis, based on a bibliographical review on the topic that refers to studies on body image and adolescence. To make this possible, the research relies on the concepts of the unheimlich and the instances of the real, the symbolic, and the imaginary, in a problematization of contemporary adolescence, which has as its research object the impasses of adolescence in the face of the estrangement of the body. The path taken by the dissertation was the understanding of the function of the image that is part of the construction of the idea of self in puberty, with the modification of the body, which involves losses of the childhood body image, as well as the gains and the assimilation of the characteristics of an adult. Thus, adolescents are faced with this form of re-actualization, which would imply a new identification of themselves, and an elaboration of the mourning of the child’s body. Faced with this reality that permeates the body, the aesthetic ideal ends up gaining prominence, as it appears to be an imaginary covering, becoming a trap that leads the subject to conform himself with image body to the aesthetic standard. For psychoanalysis, the subject articulates himself through his body, which has consistency in the imaginary, is supported by the symbolic, in addition to being crossed by the real. Such instances are articulated around the empty function of object a. For the body to consist, while the adolescent inhabits it, it is necessary to support the empty function of this object. We concluded that, for the subject to emerge, he will need to separate himself from this discursive position that totally alienates him from ideals, so that he articulates, from the chain of signifiers, a semi-saying about his experience of subjectivation, whether in front of imposed standards, whether in the face of your experience of strangeness about your body.